A physically-based numerical model of river channel widening - Darby, Stephen E. (1994)
The application of many existing numerical models of river channel morphology is limited by their inability to account for bank erosion and changing channel width through time. In this research, a physically-based numerical model which simulates the evolution of channel morphology, including channel width, through time has been developed and tested. Predictions of channel evolution are obtained by solving deterministically the governing equations of flow resistance, flow, sediment transport, bank stability and conservation of sediment mass. The model is applicable to relatively straight, sand-bed streams with cohesive bank materials.